THE IMPORTANCE OF DEEP LEARNING TECHNOLOGIES TODAY (Modern education and development, 2025)
This article analyzes the importance of Deep Learning technologies in education today. Deep learning technologies are an advanced form of artificial intelligence that can work with large amounts of data. This technology is widely used to personalize the educational process, provide learning materials tailored to the needs of students, and develop interactive assistants. Deep learning methods also help teachers identify student achievement and analyze their learning activities. However, there are also problems in implementing these technologies, such as technical shortcomings, data security, and training teachers to work with technology. The article examines the conditions and opportunities necessary for the effective use of deep learning technologies in education.